Mutations in exon 3 of the glycogen debranching enzyme gene are associated with glycogen storage disease type III that is differentially expressed in liver and muscle. - Shen, J (1996)
Glycogen storage disease type HI (GSD-III), an autosomal recessive disease, is caused by deficient glycogen debranching enzyme (GDE) activity. Most GSD-III patients are GDE deficient in both liver and muscle (type IIIa), and some GSD-III patients have GDE absent in liver but retained in muscle (type IIIb). The molecular basis for this enzymatic variability is largely unknown. In the present study, the analysis of the GDE gene in three GSD-IIIb patients by single-strand conformation polymorphism (SSCP), DNA sequencing, restriction analysis, and family studies, revealed each of them as being a compound heterozygote for two different mutations. The first mutant alleles in all three patients involved mutations in exon 3 at amino acid codon 6 of the GDE protein. Two had an AG deletion at nucleotides 17 and 18 of the GDE cDNA (17delAG) which resulted in change of subsequent amino acid sequence and a truncated protein (25X); the other had a C to T transition at nucleotide 16 of the cDNA which changed a Glutamine codon to a stop codon (Q6X). The 17delAG mutation was also found in 8 of the 10 additional GSD-IIIb patients. The Q6X mutation was found in one of the remaining two GSD-IIIb patients. These two mutations were not found in any of the 31 GSD-IIIa patients, 2 GSD-IIId patients, nor 28 unrelated normal controls. The second mutant alleles in each of the three GSD-IIIb patients were R864X, R1228X, and W68OX. The R864X and R1228X were not unique for GSD-IIIb as they were also found in GSD-IIIa patients (frequency of 10.3% and 5.2% in Caucasian patients, respectively). Our data demonstrated that both IIIa and IIIb had mutations in the same GDE gene and established for the first time the molecular basis of GSD-III that differentially expressed in liver and muscle. The striking and specific association of exon 3 mutations with GSD-IIIb may provide insight into mechanisms controlling tissue-specific expression of the GDE gene. The identification of exon 3 mutations has clinical significance as well because it distinguished GSD-IIIb from IIIa hence permitting diagnosis from a blood sample rather than a more invasive muscle biopsy.